Two Carbohydrate-Based Natural Extracts Stimulate in vitro Pollen Germination and Pollen Tube Growth of Tomato Under Cold Temperatures - Laggoun, Ferdousse; Ali, Nusrat; Tourneur, Sabine; Prudent, Grégoire; Gügi, Bruno; Kiefer-Meyer, Marie-Christine; Mareck, Alain; Cruz, Florence; Yvin, Jean-Claude; Nguema-Ona, Eric; Mollet, Jean-Claude; Jamois, Frank; et al. (Frontiers in Plant Science, 2021)
To date, it is widely accepted by the scientific community that many agricultural regions will experience more extreme temperature fluctuations. These stresses will undoubtedly impact crop production, particularly fruit and seed yields. In fact, pollination is considered as one of the most temperature-sensitive phases of plant development and until now, except for the time-consuming and costly processes of genetic breeding, there is no immediate alternative to address this issue. In this work, we used a multidisciplinary approach using physiological, biochemical and molecular techniques for studying the effects of two carbohydrate-based natural activators on in vitro tomato pollen germination and pollen tube growth cultured in vitro under cold conditions. Under mild and strong cold temperatures, these two carbohydrate-based compounds significantly enhanced pollen germination and pollen tube growth. The two biostimulants did not induced significant changes in the classical molecular markers implicated in pollen tube growth. Neither the number of callose plugs nor the CALLOSE SYNTHASE genes expression were significantly different between the control and the biostimulated pollen tubes when pollens were cultivated under cold conditions. PECTIN METHYLESTERASE (PME) activities were also similar but a basic PME isoform was not produced or inactive in pollen grown at 8°C. Nevertheless, NADPH oxidase (RBOH) gene expression was correlated with a higher number of viable pollen tubes in biostimulated pollen tubes compared to the control. Our results showed that the two carbohydrate-based products were able to reduce in vitro the effect of cold temperatures on tomato pollen tube growth and at least for one of them to modulate reactive oxygen species production.